2020
DOI: 10.1175/jpo-d-20-0028.1
|View full text |Cite
|
Sign up to set email alerts
|

The Western Alboran Gyre: An Analysis of Its Properties and Its Exchange with Surrounding Water

Abstract: One of the largest and most persistent features in the Alboran Sea is the Western Alboran Gyre (WAG), an anticyclonic recirculation bounded by the Atlantic Jet (AJ) to the north and the Moroccan coast to the south. Eulerian budgets from several months of a high-resolution model run are used to examine the exchange of water across the Eulerian WAG’s boundary and the processes affecting the salinity, temperature, and vorticity of the WAG. The volume transport across the sides of the WAG is found to be related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Peliz et al (2013) also found that cyclonic mesoscale eddies in the AS (of ∼13 km) were most common in winter, outnumbering by far anticyclonic eddies. This links with the result of Brett et al (2020), who noted a slow decay of the WAG by advection of cyclonic vorticity into the gyre. The decay of the WAG in winter could be hence related to the dominance of cyclonic eddies (and the consequent cyclonic vorticity anomaly) in the basin.…”
Section: Mesoscale and Seasonal Variabilitysupporting
confidence: 81%
See 1 more Smart Citation
“…Peliz et al (2013) also found that cyclonic mesoscale eddies in the AS (of ∼13 km) were most common in winter, outnumbering by far anticyclonic eddies. This links with the result of Brett et al (2020), who noted a slow decay of the WAG by advection of cyclonic vorticity into the gyre. The decay of the WAG in winter could be hence related to the dominance of cyclonic eddies (and the consequent cyclonic vorticity anomaly) in the basin.…”
Section: Mesoscale and Seasonal Variabilitysupporting
confidence: 81%
“…The renewal of Atlantic Water in the WAG would help maintain its horizontal density gradient with ambient waters and thereby its geostrophic motion via thermal wind balance. Brett et al (2020) have recently shown from the numerical simulation of a quasi-steady WAG that its low salinity and warm temperature signals, as well as its negative vorticity budget, are not held constant but are gradually eroded by advection of ambient Modified Atlantic Water into the gyre. The salinity minimum at the center of the WAG identified by Viudez and Haney (1997) would originate from its early formation in its loop-current stage to later decay over time.…”
Section: Origin and Maintenance Of The Mean Circulationmentioning
confidence: 99%
“…In order to investigate the dynamics of the gyre flow field in more detail, the effects of the different terms in the momentum equation are considered. For this, the vertically averaged horizontal momentum equation over the depth layers influenced by the gyre velocity field (i.e., the thermocline layer and epilimnion) is expressed as (Brett, 2018;Brett et al, 2020;Cimatoribus et al, 2018;Vallis, 2017):…”
Section: Nonlinear Dynamics Associated With a Cyclonic Gyrementioning
confidence: 99%
“…The basic idea is that a lobe, defined by two consecutive intersection points of the same two manifolds and the manifold segments in between, moves from outside to inside the area of interest. This kind of calculation works best in idealized, e.g., [9,24], or slowly evolving flows, e.g., [25,26], where the manifolds are sharply defined. However, in the present case, this methodology is complicated in part of the parameter space by the hyperbolic regions in the FTLE field being relatively weak and not stationary (see Section 3 and Figure 3), while for different parameter choices, multiple ridges appear in close proximity (not shown), making the problem prone to numerical errors.…”
Section: Transport Quantificationmentioning
confidence: 99%